PENGEMBANGAN KETERAMPILAN SISWA SMK UNTUK DUNIA KERJA MELALUI WORKSHOP CUSTOMER SERVICE EXCELLENCE DAN VIRTUAL ASSISTANT: studi kasus : SMK Mutiara Bangsa Tajur Halang kabupaten Bogor - Kusmayanti, Kusmayanti; Prasetyo, Karno Ganjar (Jurnal Pengabdian Bukit Pengharapan, 2024)
This Community Service Program (PkM) aims to develop the skills of Mutiara Bangsa Vocational School students in facing the world of work through Customer Service Excellence and Virtual Assistant workshops. This activity is carried out with an approach based on improving service quality and utilizing digital technology, in accordance with current industry needs. Students are trained to understand professional customer service concepts, such as responsiveness, empathy and reliability, and are given practical skills in operating virtual assistant technology. The results of the training show a significant increase in student competency, which is expected to build their confidence to compete in a competitive job market. This program contributes to improving the quality of vocational education and preparing students for the world of work with more relevant and applicable skills.